2014
DOI: 10.1016/j.postharvbio.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenoloxidase activity and browning in fresh-cut ‘Rocha’ pear as affected by pH, phenolic substrates, and antibrowning additives

Abstract: The effect of pH, phenolic substrates, and food additives on polyphenoloxidase (PPO) activity and on tissue browning was studied in fresh-cut 'Rocha' pear. Substrates 4-methylcatechol, caffeic acid, (+)catechin hydrate, catechol, chlorogenic acid, dopamine hydrochloride, and pyrogallol, were prepared in citric acid-phosphate buffer at pHs ranging from 3.0 to 8.0. pH optima for PPO activity depended on the phenolic substrate. Activity was optimal at pH 5.0 for catechol and 4-methylcatechol; pH 6.0 for chlorogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Additionally, any evident antibrowning effect was observed on the zymogram of Abate pear PPO and on pear slices (Figure e) probably because of the low pH of the unripe grapes. In this regard, Gomes et al () demonstrated that the browning in fresh‐cut Rocha pear was not reduced by low pH values in the presence of catechol substrate. The variable antibrowning performance among plant PPOs confirmed that the inhibitory effectiveness was mainly related to the enzyme source, as spectrophotometrically demonstrated by some authors (Zocca et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, any evident antibrowning effect was observed on the zymogram of Abate pear PPO and on pear slices (Figure e) probably because of the low pH of the unripe grapes. In this regard, Gomes et al () demonstrated that the browning in fresh‐cut Rocha pear was not reduced by low pH values in the presence of catechol substrate. The variable antibrowning performance among plant PPOs confirmed that the inhibitory effectiveness was mainly related to the enzyme source, as spectrophotometrically demonstrated by some authors (Zocca et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The main agent responsible is polyphenol oxidase or tyrosinase (PPO; EC 1.10.3.1), a copper‐containing oxidoreductase that catalyses two different reactions involving the oxidation of phenolic substances and subsequent production of quinones that polymerise to brown pigments known as melanins (Seo et al ). The degree of browning is related to the type and concentration of endogenous phenolic substances; presence of oxygen, reducing substances and metallic ions; pH; and temperature that affects PPO activity (Nicolas et al , Gomes et al ). The enzyme reaction in agro‐food products leads not only to colour alteration but also to a reduction in the nutritional and sensory quality as a consequence of quinone condensation with amino acids and proteins (Rapeanu et al ) and of the degradation of phenolic substances, substrates recognised for their health benefits as antioxidants (Quideau et al , Mihaylova et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of browning intensity was performed according to Nguyen et al [40]. The potato polyphenol oxidase activity was determined using the method described by Gomes et al [41] for the use of a 100 mM citrate acid-200 mM sodium phosphate buffer between pH 3.0 and 8.0. The enzyme extract (0.5 mL) was added to the quartz test tube and a buffer solution containing phenolic substrate (2.5 mL) was added.…”
Section: Collection and Analysis Of Soil Samples And Potato Tuber Sammentioning
confidence: 99%
“…Sometimes, the CWC is also washed, peeled, sliced and packaged before being marketed as a ready-to-eat product. However, most of fruit and vegetables turn brown after being peeled (Sagar & Kumar, 2010), such as apples (Luo, Lu, Zhou, & Feng, 2011), pears (Gomes et al, 2014) and potatoes (ZvitovYa'ari & Nussinovitch, 2014). In contrast with other fruit and vegetables, fresh-cut CWC is prone to etiolation, reducing its shelf life and its commercial value (Ma, Wang, Hong, & Cantwell, 2010;Oms-Oliu et al, 2010;You et al, 2012).…”
Section: Introductionmentioning
confidence: 99%